Development of an advanced nano-satellite VELOX-I-study of high speed motion detection CMOS image sensor design - Huang, Jing (2014)
This final year project is one part of the VELOX-I satellite series projects. After launching Singapore’s first two home developed satellites, VELOX-I nano-satellite has been scheduled to launch next. Image sensor is a part of the subsystems as one of the main functions of the satellite is to take pictures of the aerospace. In a conventional image sensor, the readout circuit is controlled by a clock and sequentially reads out the pixel value regardless of the pixels’ activeness. The conventional readout circuit is short of speed since most pixels are inactive in aerospace.